카오스 이론을 이용한 2상 유동 해석 - 權正泰(Jeong-Tae Kwon); 權寧哲(Young-Chul Kwon); 金景敏(Kyoung-Min Kim) (전기학회 논문지 P권, 56(1), 2007)
This article presents a review on chaos analysis of two-phase flow. Chaos theory has recently been applied to two-phase flow analysis, and it gives promising measures to quantitatively identify two-phase flow patterns and pool boiling behaviors. But, consistency of the calculated chaotic measures were not completely confirmed yet. More experimental data are requested for chaos analysis of two-phase flow. Also, chaos analysis methodology should be developed by experimental verification.